Management and its impact on productivity in the Philippine work setting of food and garments industries - Martires, Concepcion R. (The Philippine Review of Business and Economics, 1988)
The study investigates the impact on productivity of selected management variables namely: motivational strength, satisfaction level, commitment level, leadership style and management level. Data are gathered principally through a survey conducted among managers and supervisors in food and garments firms in Metro Manila. The results of the survey show that moderate to strong relationships were exhibited when the independent variables were correlated with the objective measures of productivity, while subjective measures of performance showed very weak correlation with the independent factors, even when taken together. Based on its findings, the paper ventures several recommendations which include, among others, a continuing dialogue between owners, top executives, and middle managers; the improvement of leadership styles among managers towards greater task0and people-orientation; and measures leading to reduction of the communication gap between top managers and middle management. Furthermore, the paper proposes that similar studies be conducted in other industries, and points out the at areas which future studies can further explore to clarify and/or validate the results obtained thus far.